Comparison of organic (UK'37, TEXH86, LDI) and faunal proxies (foraminiferal assemblages) for reconstruction of late Quaternary sea surface temperature variability from offshore southeastern Australia. (2nd August 2013) - Lopes dos Santos, Raquel A.; Spooner, Michelle I.; Barrows, Timothy T.; De Deckker, Patrick; Sinninghe Damsté, Jaap S.; Schouten, Stefan
<x xml:space="preserve">Abstract</x> [1] Several proxies have been developed to reconstruct past sea surface temperature (SST), but different proxies may reflect temperatures of different seasons and each proxy is characterized by certain uncertainties. Therefore, a multiproxy approach is preferred to precisely reconstruct SST. Here, we reconstruct SST of the ocean offshore southeastern Australia (Murray Canyons area) for the last ~135 ka using three independent organic proxies (TEXH86 based on glycerol dialkyl glycerol tetraethers (GDGTs), UK'37 based on alkenones, and LDI based on long‐chain diols) in addition to foraminiferal faunal assemblages. The organic proxy records show similar trends, with the highest temperature (21°C for UK'37 and TEXH86, and 25°C for LDI) during the last interglacial and lowest temperature (8°C for TEXH86, 10°C for UK'37, and 12°C for LDI) during the Last Glacial Maximum. However, the differences in absolute SST estimates obtained by the organic proxies varied over time with differences of up to 9°C between LDI and TEXH86. The seasonal SST reconstructions based on the modern analogue of foraminiferal assemblages also show similar trends as the organic proxies with highest temperatures during the last interglacial (23°C for the warmest month SST, 20°C for mean annual, and 18°C for the coolest month) and lowest temperature during the Last Glacial Maximum (14°C for the warmest month, 11°C for mean annual, and 9°C for the coolest month). Down core comparison between the reconstructed SSTs of the organic and inorganic proxies shows that LDI‐inferred temperatures compare well with the temperature of the warmest month, TEXH86 with the temperature of the coolest month, and UK'37 with mean annual temperature. An increase in TEXH86 SST estimates relative to those of other proxies during deglaciations and interglacials suggests that either winter temperatures rapidly warmed, possibly due to an invigoration of the Leeuwin Current over the core site, or there was a change in the growth season of the Thaumarchaeota, the source organism of GDGTs. Our study shows the benefits of a multiproxy approach in the interpretation of SST proxies, leading to a more robust knowledge of past ocean temperature changes.